Penapisan Cendawan Antagonis Indigenos Rizosfer Jahe dan Uji Daya Hambatnya terhadap Fusarium oxysporum f. sp. zingiberi - Nurbailis Nurbailis; Winarto Winarto; Afriani Panko (Jurnal Fitopatologi Indonesia, 2015)
Ginger rot disease caused by Fusarium oxysporum f. sp. zingiberi is difficult to control because the pathogen is soil borne and is able to form clamidospore as resting structure. The aim of this study was to obtain indigenous antagonistic fungi from ginger rhizosphere which is potential for suppressing the growth of F. oxysporum f. sp. zingiberi. Fungi isolated from ginger rhizosphere were subjected for antagonism assay using dual culture method. Fungi isolates showed capability to inhibit F. oxysporum f. sp. zingiberii were then identified based on morphology characters. Eleven isolates were successfully isolated, but only 9 isolates showed the potentials of suppressing the growth of F. oxysporum f. sp.  zingiberi. All 9 isolates i.e. AB4, GC1, BB1, AB1, AB2, K12, GC3, K11 and GC2 had antibiosis activity, and 3 isolates among them i.e. AB2, BB1 and K11 showed competition mechanism. Based on morphology characters the isolates were identified as Penicillium spp. (4 isolates), Trichoderma spp. (3 isolates), and Aspergillus spp. (2 isolates).